A New Experimental Animal Model of Chronic Cervical Compressive Myelopathy. (May 2014) - Zihe, L.; Zhongjun, L.; Gengding, D.; Feng, W.
Introduction: Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord dysfunction among adults over the age of 55?In China the morbidity of CSM is 10%. However, the pathobiology of CSM is still unclear which limits therapeutic advances for this common cause of neurological dysfunction. The clinical course of the disease remains unpredictable. The lack of reliable animal models of CSM has been a restriction to advancing the field. Up to now, various animal model of CSM have been made. Although some of these studies have impressive progress, they also have significant defects. Many of these models fail to model the chronic and progressive nature of the disease since they do not accurately reproduce the main human neuropathological and clinical features of CSM, In this study we report a new model of CSM in sheep. It is more accurate and stable than previous models. Moreover, the entire course of compression is digitized. Materials and Methods: A Silicone sealed compression device is assembled with a stepping motor, gear reducer and a push rod. The compression device is connected to a circuit board which contains a bluetooth module and a control chip. Power supply is a lithium battery. Circuit board is also well sealed with silicone. It is controlled via an Android cellphone in vitro. Six male small tailed han sheep were divided into two groups randomly, four in experimental group and two in control group. The compression device was implanted into intervertebral space of C4/C5 and fixed. Circuit board was implanted subcutaneously. The control group ran no compression after surgery. Animals of each group were carried on a routine CT inspection right after the surgery. The front end of the push rod was adjusted to the posterior edge of the cervical vertebral. The experimental group pushed 0.4 mm each week while awake. Tarlov scores were assessed in each group before and after push. Results: In the course of the experiment, one sheep of the experimental group appeared malfunction of the circuit board subskin. The dysfunctional board was replaced during an extra operation. The Tarlov sores of the experimental group didn't change before and after each time of push. No behavioral changes were noted in control group. While sheep in the experimental group showed gradually changes of gait. The final Tarlov score was four in three sheep and three in one sheep of the experimental group and the final radiological findings showed that the average spinal canal encroachment rate was 60.6% in the experimental group after 18 weeks' observation. Conclusion: This animal model can be used to generate controllable compression to spine operated by a digitized system. No invasive procedures were applied during the experiment. In next stage of experiment we could get specimens and run pathological tests. Disclosure of Interest None declared